Integrated process simulation for bioethanol production: Effects of varying lignocellulosic feedstocks on technical performance. (May 2021) - Morales, Marjorie; Arvesen, Anders; Cherubini, Francesco
Highlights: Feedstock-specific data for bioethanol production support more accurate assessments. Seven lignocellulosic biomasses were analyzed. Detailed process simulation of bioethanol production was performed. Feedstock type affects conversion performances and mass/energy balances. Feedstock carbohydrate content is the main driver of energetic efficiency. Abstract: Variations in lignocellulosic feedstock composition can influence conversion performance of bioethanol production, but such effects are overlooked in several studies that rely on standard conversion factors. This study investigates the effects of seven lignocellulosic feedstocks (belonging to the categories energy crops, forest and agricultural residues) on mass, carbon, water and energy balances for biochemical bioethanol production, including a comparison of individual process step yields. We find that overall bioethanol yields vary considerably, ranging between 19.0 and 29.0%, 27.3 and 46.2%, and 19.0 and 31.0%, for energy and carbon efficiency, respectively. The highest yields are found for switchgrass, which has the largest carbohydrate content, and the lowest for forest residues (spruce). Feedstock composition also affects water and carbon balances. Overall, the type of biomass influences conversion performances, thereby calling for explicit representation of the effects of biomass types in technical, economic and environmental assessment studies of bioethanol production.